Analysis and Simulation of Engagement Process of Jaw Type Electromagnetic Clutch - Chuang Yang; Xiaoping Su; Dashuang Zhou; Qiqi Wu (Jixie chuandong)
The working principle of the jaw type electromagnetic clutch is introduced， then the dynamic engagement process of the end face teeth is analyzed in detail. The engagement of the end face teeth with different speed difference is explored. Through theoretical calculation， the maximum speed difference of the clutch could engage is obtained. Through Adams virtual prototype simulation method， the influence of different speed difference on clutch engagement time and impact force is obtained. Simultaneously， the maximum speed difference of clutch smoothly engaging and the result of theoretical calculation are verified. The research provides a reference for the practical application and design improvement of the jaw type electromagnetic clutch.